A Systematic Literature Review on Career Development and Millennial Retention: Exploring the Roles of Job Satisfaction, Organizational Commitment, and Employee Empowerment - Jannah, Ni'matul (Journal of Idealistic Human Resources, 2025)
Objective: This study aims to systematically examine four key factors that influence millennial retention in organizations—career development, job satisfaction, organizational commitment, and employee empowerment—and to develop a conceptual framework as a reference for human resource management practitioners. Research Design & Methods: The results of the study indicate that career development is the factor most frequently associated with millennial retention. Job satisfaction acts as a mediator between working conditions and retention intentions. Organizational commitment, particularly affective commitment, is strengthened by an inclusive work culture and aligned organizational values. Employee empowerment plays a mediating and moderating role in the relationship between leadership, work engagement, and innovative behavior. Studies indicate that the combination of these four factors has a significant impact on the loyalty and performance of young employees. These findings emphasize that retention cannot be achieved through a single approach. Findings: This study suggests that HR policies should be redesigned with a focus on the work experience of millennials. Organizations need to develop personalized career programs, make job satisfaction a strategic indicator, build commitment through participatory leadership, and integrate empowerment into the work culture. Retention strategies should be based on values, the meaning of work, and recognition of individual contributions. Implications & Recommendations: This study provides conceptual contributions in the form of systematic mapping of the relationships between key variables in millennial retention. The added value of this study is the integration of psychological and structural approaches in retention strategies. This study also reinforces the importance of literature synthesis as the basis for evidence-based HR policy formation. The results can be used as a basis for developing more generationally relevant retention intervention models. Contribution & Value Added: This research contributes by systematically mapping key variables for millennial retention, integrating psychological and structural approaches as a basis for developing human resource policies and generational intervention models.